2007
DOI: 10.1590/s0104-56872007000300005
|View full text |Cite
|
Sign up to set email alerts
|

Programa de triagem auditiva neonatal: associação entre perda auditiva e fatores de risco

Abstract: TEMA: perda auditiva em neonatos. OBJETIVOS: verificar a prevalência de alterações auditivas em neonatos do Hospital São Paulo, observando se há correlação com as variáveis: peso de nascimento, idade gestacional, relação peso e idade gestacional e fatores de risco para deficiência auditiva. MÉTODO: realizou-se uma análise retrospectiva dos prontuários de 1696 recém nascidos, sendo 648 nascidos pré-termo e 1048 a termo. Todas as crianças foram submetidas à avaliação audiológica constituída por pesquisa das emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
1
21

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 15 publications
9
29
1
21
Order By: Relevance
“…This result was similar to that found by Pereira et al (15) , who observed 36% in their sample as being ICU leavers. Additionally, in the study by Pereira et al (15) , the association between hearing impairment and risk factors in public hospitals for pre-term newborns were: low weight/small size for gestational age, followed by ototoxicity and mechanical ventilation.…”
Section: Discussionsupporting
confidence: 92%
“…This result was similar to that found by Pereira et al (15) , who observed 36% in their sample as being ICU leavers. Additionally, in the study by Pereira et al (15) , the association between hearing impairment and risk factors in public hospitals for pre-term newborns were: low weight/small size for gestational age, followed by ototoxicity and mechanical ventilation.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown samples with more than 10% of newborns with RIHI, confirming this evidence when it came to the presence of the indicator in the following studies: 12% 12 ; 29% 14 ; and 6%, 12% and 14% 15 .…”
Section: Discussionsupporting
confidence: 70%
“…Other authors have also reached the same conclusion [15][16][17][18][19] . Another study also relates this indicator with a population of low risk NB 8 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Technological advances and public policies allow for a transformation in the panorama of the quality of life of these children, as there is the possibility of detection of hearing loss and early intervention [7][8][9][10][11] . The early forwarding of hearing impaired children to a language therapy intervention program becomes a preventative action against the secondary alterations of hearing impairment [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%